Diversifying the bench: Applying social cognitive theories to enhance judicial diversity. Issue 2 (24th December 2020) - Carroll, Ellen M.; Walker, Tammi D.; Croft, Alyssa
Abstract: White men remain overrepresented in the American judiciary (i.e., the bench) despite increasing demographic diversity among law students and lawyers. Augmenting efforts to tackle systemic barriers, a social cognitive process model integrating Goal Congruity and Cultural Mismatch Theories to partially explain why women, first‐generation, and underrepresented racial minority (URM) lawyers are less likely to pursue and thrive in judicial roles was proposed. The unexplored misalignment between the goals and values typically endorsed by eligible underrepresented judicial candidates and their perceptions of judgeship was addressed. Specifically, women, first‐generation, and URMs tend to endorse primarily communal/interdependent goals and values, while judgeship is viewed as a stereotypically agentic/independent profession. Thus, judicial diversity could be enhanced by (1) highlighting role attributes that are aligned with communal/interdependent values and (2) increasing appreciation for existing judicial communality/interdependence. It was concluded by providing hypothesized interventions to target key psychological mechanisms along the "leaky pipeline" to the judiciary.